New aspects of quantity surveying practice : a text for all construction professionals - Cartlidge, Duncan (Hoboken, New Jersey : Taylor & Francis, 2002)
The past decade has seen dramatic changes in the construction industry and the quantity surveying profession. The Latham and Egan reports and a client-led crusade for value for money is driving Quantity Surveyors to adopt these changes. In addition, the industry and the profession now stands on the threshold of the e-commerce revolution - one which has so far failed to penetrate the working practices of the majority of surveyors, particularly SMEs. Duncan Cartlidge addresses the evolving market in which today's Quantity Surveyors work, examining the new construction culture, new procurement str.
1. The Catalyst of Change-- 2. Managing Value. Part 1: The Supply Chain-- 3. Managing Value.-- Part 2: Partnering-- 4. Procurement -- Doing Deals; 5. Procurement -- Doing Deals Electronically; 6. New Technology -- Opportunity or Threat?; 7. Global Markets -- Making Ends Meet; 8. Education, Research and Practice
Includes index.
Keywords: QUANTITY SURVEYING